PERBANDINGAN KEPASTIAN HUKUM TRANSSEKSUAL ANTARA NEGARA REPUBLIK INDONESIA DAN REPUBLIK ISLAM IRAN (Mimbar Keadilan, 2022)
This writing aims to legal reconstruction the law in Indonesia where the Islamic Republic of Iran is a comparison country. The method used is a functional method in comparative law through the approach of legal institutions and bodies of norms. Based on this legal comparison, it was found that homosexuality is an act that is very contrary to religious and cultural norms and common sense, so transsexuality with very strict terms and conditions is an urgent solution. Indonesia and Iran only recognize two genders, namely male and female. However, in Indonesia, it is not specifically regulated regarding lesbian, homosexual, and transsexual sexual acts. The existence of different judicial decisions in Indonesia regarding transsexuals shows that these decisions do not meet the elements of jurisprudence. In addition, the absence of laws and regulations specifically regulating transsexuals necessitates the absence of legal standardization of basic norms in the state so that the Constitutional Court cannot carry out its function as the protector of human rights and the final interpreter of the constitution. There needs to be an association under the auspices of the government that specifically handles sexual disorders and transsexual issues. In addition, considering that the main source of law in countries with a civil law tradition is the law (formal rules), it is necessary to establish a law that specifically regulates transsexuals as a manifestation of the principle of legal certainty and the principle of consensus as well as legal standardization of actions, handling, regulations, and legal consequences imposed on transsexual issues.